PERANCANGAN APLIKASI PENDETEKSI STUNTING PADA BALITA DENGAN AUGMENTED REALTY - Dofariando, Muhammad Ariel; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2025)
Stunting is a form of chronic malnutrition that causes impaired growth and development in children under five, especially in their first 1,000 days of life. The high prevalence of stunting in Indonesia, despite national reduction efforts, demands more effective and innovative early detection solutions. Conventional anthropometric measurements are still carried out manually and often overlooked by the public due to lack of awareness and tools. This research aims to design and implement an Android-based application utilizing Augmented Reality (AR) technology to assist in early detection of stunting in toddlers. The application uses the WHO Z-score Height-for-Age standard and camera-based real-time measurement with AR support on devices equipped with Time-of-Flight (ToF) sensors. The study applied a structured development methodology and was implemented using Unity and ARCore SDK. Users input the child’s age and weight, then scan the child’s height with their device, and the system automatically classifies stunting status visually and informatively. Testing showed that the application achieved an accuracy rate of approximately 99% at optimal lighting and scanning distance, with successful rendering of 2D and 3D objects. It also proved effective in raising awareness by offering educational content such as interactive visualizations, growth graphics, and parenting tips. The results confirm that the AR-based stunting detection application is functional, user-friendly, and informative, providing both a diagnostic tool and a medium for public health education. It supports government stunting reduction programs and empowers parents and healthcare workers in remote or underserved areas.